(untitled) (Colombia Medica, 2025)
Cutaneous leishmaniasis is a neglected tropical disease caused by Leishmania species and transmitted by the bite of infected female sandflies. It primarily affects the skin and mucous membranes, with a broad spectrum of clinical manifestations that depend mainly on the host’s immune response. The immune balance between Th1, Th17, and Th2 pathways plays a pivotal role in disease progression and outcome. Hyperergic responses (Th1/Th17) are associated with localized and mucosal forms, while anergic responses (Th2/Treg) underline disseminated and diffuse cutaneous forms. Despite its global prevalence, particularly in tropical and subtropical regions, cutaneous leishmaniasis remains underdiagnosed and mismanaged due to limited awareness of its immunopathogenesis, clinical diversity, and diagnostic limitations. Treatment continues to rely primarily on pentavalent antimonial compounds, which have significant toxicity, underscoring the urgent need for safer and more effective therapeutic alternatives. This narrative review examines the immune response, clinical manifestations, diagnostic methods, and medical management strategies for cutaneous leishmaniasis. Understanding the complex interplay between immune responses and clinical manifestations is essential for improving diagnosis and treatment